Perancangan E-Voting berbasis Web - Nurul Azwanti (Politeknik Caltex Riau, 2017)
One form of democracy is marked by direct election of the President, Governor, Mayor, Regent to the election of the Chairman of the Rukun Warga and Rukun Tetangga. Rukun Tetangga or commonly abbreviated as RT is the area under Rukun Warga (RW). Each RT is led by the RT Chairperson whose election is also conducted based on local community deliberations. In RT 08 the election of RT head has been done in February 2017 with candidate amounted to 3 people. However, people's ignorance of the number of ballot papers provided also raises question marks because they are not transparent and too hasty. Unlike traditional calculations, e-voting or electronic voting has advantages such as accuracy, convenience and ease of use. The modeling used is UML (Unified Modeling Language) which will give description about the system to be built. UML to be used include, Use Case Diagrams, Class Diagrams, Activity Diagrams and Deployment Diagrams. The design of e-voting at RT 08 is expected to cover the weakness in manual voting system (traditional). Web support also provides easy access to the community in finding information about candidates or nominees RT chairman.